Adjusting Your Dreams? High School Plans and Dropout Behaviour1. (6th July 2016) - Goux, Dominique; Gurgand, Marc; Maurin, Eric
Abstract : At the end of middle school, many low‐achieving students realise that they do not have the ability to get into selective high school programmes, which may be a source of disengagement and eventually lead them to drop out of high school. Based on a randomised controlled trial, this article shows that a series of meetings facilitated by the school principals can help low‐achievers to formulate educational objectives better suited to their academic aptitudes. By changing the high school plans of the less realistic students, the intervention reduces grade repetition and dropout by 25% to 40%.